Reciprocal interaction of dendrite geometry and nuclear calcium-VEGFD signaling gates memory consolidation and extinction - Hemstedt, Thekla Joana; Bengtson, C. Peter; Oliveira, Ana; Bading, Hilmar (The journal of neuroscience, 2017)
Nuclear calcium is an important signaling end point in synaptic excitation-transcription coupling that is critical for long-term neuroadaptations. Here, we show that nuclear calcium acting via a target gene, VEGFD, is required for hippocampus-dependent fear memory consolidation and extinction in mice. Nuclear calcium-VEGFD signaling upholds the structural integrity and complexity of the dendritic arbor of CA1 neurons that renders those cells permissive for the efficient generation of synaptic input-evoked nuclear calcium transients driving the expression of plasticity-related genes. Therefore, the gating of memory functions rests on the reciprocally reinforcing maintenance of an intact dendrite geometry and a functional synapse-to-nucleus communication axis. In psychiatric and neurodegenerative disorders, therapeutic application of VEGFD may help to stabilize dendritic structures and network connectivity, which may prevent cognitive decline and could boost the efficacy of extinction-based exposure therapies. SIGNIFICANCE STATEMENT: This study uncovers a reciprocal relationship between dendrite geometry, the ability to generate nuclear calcium transients in response to synaptic inputs, and the subsequent induction of expression of plasticity-related and dendritic structure-preserving genes. Insufficient nuclear calcium signaling in CA1 hippocampal neurons and, consequently, reduced expression of the nuclear calcium target gene VEGFD, a dendrite maintenance factor, leads to reduced-complexity basal dendrites of CA1 neurons, which severely compromises the animals' consolidation of both memory and extinction memory. The structure-protective function of VEGFD may prove beneficial in psychiatric disorders as well as neurodegenerative and aging-related conditions that are associated with loss of neuronal structures, dysfunctional excitation-transcription coupling, and cognitive decline.
Gesehen am 04.05.2018